Hypothalamic atrophy is related to body mass index and age at onset in amyotrophic lateral sclerosis. Issue 12 (8th June 2017) - Gorges, Martin; Vercruysse, Pauline; Müller, Hans-Peter; Huppertz, Hans-Jürgen; Rosenbohm, Angela; Nagel, Gabriele; Weydt, Patrick; Petersén, Åsa; Ludolph, Albert C; Kassubek, Jan; Dupuis, Luc
Abstract : Objective: Our objective was to study the hypothalamic volume in a cohort of patients with amyotrophic lateral sclerosis (ALS) including symptomatic and presymptomatic ALS mutation carriers. Methods: High-resolution three-dimensional T1-weighted MRI datasets from 251 patients with sporadic ALS, 19 symptomatic and 32 presymptomatic ALS mutation carriers and 112 healthy controls (HC) were retrospectivally registered for manual delineation of the hypothalamus. The volume of the hypothalamus, in total or subdivided, was normalised to the intracranial volume and adjusted to age. Correlation analyses were performed with clinical and metabolic outcomes. Pathologically defined ALS stages were determined in vivo by diffusion tensor imaging (DTI). Results: We observed a severe atrophy of the hypothalamus both in patients with sporadic ALS (−21.8%, p < 0.0001) and symptomatic ALS mutation carriers (−13.4%, p<0.001). The atrophy in patients with sporadic ALS was observed in both the anterior (−27.6% p<0.0001) and the posterior parts of the hypothalamus (−17.7%, p<0.0001). Notably, this atrophy was also observed in presymptomatic ALS mutation carriers (−15.5%, p<0.001) and was unrelated to whole brain volume atrophy or disease stage as assessed using DTI or functional status. Hypothalamic volume was correlated with body mass index (BMI) in patients with sporadic ALS (p=0.0434, ρ= +0.1579), and this correlation was much stronger in patients with familial ALS (fALS) (p=0.0060, ρ= +0.6053). Anterior hypothalamic volume was correlated with age at onset, but not with survival after MRI. Conclusions: Hypothalamus is atrophied in ALS, even in premorbid stages, and correlates with BMI, especially in fALS. Decreased anterior hypothalamic volume is associated with earlier onset of disease.